Hubungan Tingkat Stres Dengan Lama Fase Aktif Kala 1 Persalinan Pada Primigravida Di Bpm Rita - Endang Sari; Welly Handayani (Departement of Mathematics Education, 2023)
As a prospective mother, especially for the first time or first time, in the face of childbirth, you will feel afraid, causing tension which can cause disruption to uterine contractions. Psychological factors also greatly determine the success of childbirth, This research is a quantitative research with descriptive analysis method. The design used in this research is cross sectional. The population in this study were all third trimester pregnant women who were facing active phase 1 labor namely 50 pregnant women. The number of samples taken is a minimum sample of 30 samples.The results showed that 50% of mothers experienced stress and more than half of mothers experienced a fast active phase of 63.3%. Statistical tests resulted in a relationship between stress and the length of the active phase of stage 1 withp value 0,001. To the practice of midwives Hermina and other health facilities, it is recommended to further improve health education on how mothers are not stressed in dealing with childbirth, especially during stage 1.